2016
DOI: 10.1111/oik.03948
|View full text |Cite
|
Sign up to set email alerts
|

Movement tactics of a mobile predator in a meta‐ecosystem with fluctuating resources: the arctic fox in the High Arctic

Abstract: Animal movement is a fundamental process shaping ecosystems at multiple levels, from the fate of individuals to global patterns of biodiversity. The spatio-temporal dynamic of food resources is a major driver of animal movement and generates patterns ranging from range residency to migration and nomadism. Arctic tundra predators face a strongly fluctuating environment marked by cyclic microtine populations, high seasonality, and the potential availability of sea ice, which gives access to marine resources in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 85 publications
(108 reference statements)
2
44
0
Order By: Relevance
“…Thick snow cover has been suggested to reduce predation rates on lemmings (Gilg et al 2006), but a recent study found that thick snow cover only weakly limited fox predation attempts made by jumping through the snow, did not affect attempts made by digging, and did not provide lemming protection against ermine predation (Bilodeau et al 2013a). These observations suggest in years with high lemming densities, when foxes continue to occupy dens consistently during winter (Lai et al 2017), enhanced snow depth on dens may not protect lemmings from predators and predation risk on dens could be high. In such years, fox dens may act as ecological traps (reviewed in Hale and Swearer 2016), where net fitness is reduced by increased predation risk despite the benefits of enhanced thermal protection and improved quality and quantity of forage.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thick snow cover has been suggested to reduce predation rates on lemmings (Gilg et al 2006), but a recent study found that thick snow cover only weakly limited fox predation attempts made by jumping through the snow, did not affect attempts made by digging, and did not provide lemming protection against ermine predation (Bilodeau et al 2013a). These observations suggest in years with high lemming densities, when foxes continue to occupy dens consistently during winter (Lai et al 2017), enhanced snow depth on dens may not protect lemmings from predators and predation risk on dens could be high. In such years, fox dens may act as ecological traps (reviewed in Hale and Swearer 2016), where net fitness is reduced by increased predation risk despite the benefits of enhanced thermal protection and improved quality and quantity of forage.…”
Section: Discussionmentioning
confidence: 95%
“…These observations suggest in years with high lemming densities, when foxes continue to occupy dens consistently during winter (Lai et al. ), enhanced snow depth on dens may not protect lemmings from predators and predation risk on dens could be high. In such years, fox dens may act as ecological traps (reviewed in Hale and Swearer ), where net fitness is reduced by increased predation risk despite the benefits of enhanced thermal protection and improved quality and quantity of forage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juveniles from unrelated litters used the same feeding stations and sometimes at the same time, suggesting that breeding pairs seemed to allow the juveniles from other litters at the dispensers within their territory. Temporal variation in food availability may allow a breeding pair to tolerate additional individuals in its territory at times when food abundance is high, as described in Svalbard (Eide et al 2004), Canada (Lai et al 2017), Sweden, and Iceland (Elmhagen et al 2014). It could also be that these unrelated juveniles were only visiting the feeding dispensers sporadically while dispersing, during a period when adults were less territorial.…”
Section: Discussionmentioning
confidence: 99%
“…; Lai et al. ). Birds are among the most mobile of all organisms and undertake some of the world's longest migrations, usually in predictable annual cycles (Alerstam et al.…”
Section: Introductionmentioning
confidence: 98%